Direct observation of the injection dynamics of a laser wakefield accelerator using few-femtosecond shadowgraphy - Savert; Mangles,SPD; Schnell,M; Siminos,E; Cole,JM; Leier,M; Reuter,M; Schwab,MB; Moller,M; Poder,K; Jackel,O; Paulus,GG; et al. (Physical Review Letters, 2015)
We present few-femtosecond shadowgraphic snapshots taken during the non-linear evolution of the plasma wave in a laser wakefield accelerator with transverse synchronized few-cycle probe pulses. These snapshots can be directly associated with the electron density distribution within the plasma wave and give quantitative information about its size and shape. Our results show that self-injection of electrons into the first plasma wave period is induced by a lengthening of the first plasma period. Three dimensional particle in cell simulations support our observations.